Direct electron transfer of fructose dehydrogenase immobilized on thiol-gold electrodes. (1st October 2021) - Yan, Xiaomei; Ma, Su; Tang, Jing; Tanner, David; Ulstrup, Jens; Xiao, Xinxin; Zhang, Jingdong
Abstract: Direct electrochemical electron transfer (DET) of oxidoreductases has attracted increasing attention in pure and applied bioelectrochemistry (e.g. biosensors and biofuel cells) over the last decades. We report here a systematic study of DET-type bioelectrocatalysis of the membrane-bound redox enzyme fructose dehydrogenase (FDH, Gluconobacter sp. ), on variable-length and variably terminated thiol self-assembled monolayers (SAMs) both on Au(111) and nanoporous gold (NPG) electrodes. FDH on Au(111) modified by short-chain moderately hydrophilic 2-mercaptoethanol (BME) SAMs exhibits the highest DET activities and largest DET-capable fraction. Fitting of theoretical polarization curves to the data and homology modeling/docking of FDH offer further mechanistic insight. The dependence of the DET efficiency of FDH on the length and differently terminated carbon chain is systematically presented. The decreased DET rate with increasing chain length is associated with increasingly unfavourable long-range electron tunnelling, and not with lowered enzyme loading. The porous structure of NPG is favorable for FDH bioelectrocatalysis by improving both efficient enzyme orientation and operational stability. Overall, our study maps systematically the controlled local environmental structural flexibility of the Au/SAM/enzyme/solution interface, a paradigm for thiol modified surfaces in biosensors and bioelectronics. Graphical abstract: Image, graphical abstract